2007
DOI: 10.1016/j.jacc.2006.10.075
|View full text |Cite
|
Sign up to set email alerts
|

Unique Autonomic Profile of the Pulmonary Veins and Posterior Left Atrium

Abstract: The PVs and PLA demonstrate unique activation and repolarization characteristics in response to autonomic manipulation. The heterogeneity of vagal responses correlates with the pattern of IKAch distribution in the LA. The peculiar autonomic characteristics of the PVs and PLA might create substrate for re-entry and AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 17 publications
5
55
0
Order By: Relevance
“…38 Interestingly, adrenergic and cholinergic epicardial nerve and muscarinic receptor densities as well as I K(ACh) heterogeneity are relatively higher in the canine posterolateral LA wall. 37,38 When the early tachyarrhythmias beats originated from (1) the posterolateral LA wall next to the left PVs or (2) Bachmann bundle insertion into the superior RA wall, repolarization changes were concentrated in the atrial regions in which the tachyarrhythmia sites of origin were identified.…”
Section: Relation To Neural Influences On the Atriamentioning
confidence: 94%
See 1 more Smart Citation
“…38 Interestingly, adrenergic and cholinergic epicardial nerve and muscarinic receptor densities as well as I K(ACh) heterogeneity are relatively higher in the canine posterolateral LA wall. 37,38 When the early tachyarrhythmias beats originated from (1) the posterolateral LA wall next to the left PVs or (2) Bachmann bundle insertion into the superior RA wall, repolarization changes were concentrated in the atrial regions in which the tachyarrhythmia sites of origin were identified.…”
Section: Relation To Neural Influences On the Atriamentioning
confidence: 94%
“…38 Interestingly, adrenergic and cholinergic epicardial nerve and muscarinic receptor densities as well as I K(ACh) heterogeneity are relatively higher in the canine posterolateral LA wall. 37,38 When the early tachyarrhythmias beats originated from (1) the posterolateral LA wall next to the left PVs or (2) Bachmann bundle insertion into the superior RA wall, repolarization changes were concentrated in the atrial regions in which the tachyarrhythmia sites of origin were identified. The tachyarrhythmia sites of origin identified in the posterolateral LA wall (most frequently associated with left dorsal mediastinal nerve stimulation) were adjacent to the ligament of Marshall (which includes predominantly cholinergic neural elements in the canine heart 39 as well as to the LA and dorsal atrial ganglionated plexuses.…”
Section: Relation To Neural Influences On the Atriamentioning
confidence: 94%
“…It is known that the pulmonary vein as well as the atrium is densely innervated by the autonomic nerves (19,20), and parasympathetic nerve activation usually encourages reentry via shortening of the effective refractory period, acting as a maintenance factor of atrial fibrillation. Indeed, in the canine model of vagally induced atrial fibrillation, ablation of the autonomic ganglia near the ostia of pulmonary vein prevented atrial fibrillation, showing the importance of cholinergic activation in the pulmonary veins for this type of atrial fibrillation (21).…”
Section: Discussionmentioning
confidence: 99%
“…Parasympathetic innervation and activation can induce and maintain atrial fibrillation, whereas ablation can induce parasympathetic denervation and improve clinical outcome. 93,94 Due to the lack of sufficient experience and data, imaging of cardiac parasympathetic system has been limited. There is a low density of cholinergic neurons in the heart, as well as difficulty in tracer design because of rapid degradation of acetylcholine by esterase and a high specificity of the presynaptic receptor system for acetylcholine.…”
Section: Imaging Of the Cardiac Parasympathetic Systemmentioning
confidence: 99%